Bi-allelic Variants in DYNC1I2 Cause Syndromic Microcephaly with Intellectual Disability, Cerebral Malformations, and Dysmorphic Facial Features. - Ansar, Muhammad; Ullah, Farid; Paracha, Sohail A; Adams, Darius J; Lai, Abbe; Pais, Lynn; Iwaszkiewicz, Justyna; Millan, Francisca; Sarwar, Muhammad T; Agha, Zehra; Shah, Sayyed Fahim; Qaisar, Azhar Ali; et al. (Am J Hum Genet, 2019)
Cargo transport along the cytoplasmic microtubular network is essential for neuronal function, and cytoplasmic dynein-1 is an established molecular motor that is critical for neurogenesis and homeostasis. We performed whole-exome sequencing, homozygosity mapping, and chromosomal microarray studies in five individuals from three independent pedigrees and identified likely-pathogenic variants in DYNC1I2 (Dynein Cytoplasmic 1 Intermediate Chain 2), encoding a component of the cytoplasmic dynein 1 complex. In a consanguineous Pakistani family with three affected individuals presenting with microcephaly, severe intellectual disability, simplification of cerebral gyration, corpus callosum hypoplasia, and dysmorphic facial features, we identified a homozygous splice donor site variant (GenBank: NM_001378.2:c.607+1G>A). We report two additional individuals who have similar neurodevelopmental deficits and craniofacial features and harbor deleterious variants; one individual bears a c.740A>G (p.Tyr247Cys) change in trans with a 374 kb deletion encompassing DYNC1I2, and an unrelated individual harbors the compound-heterozygous variants c.868C>T (p.Gln290) and c.740A>G (p.Tyr247Cys). Zebrafish larvae subjected to CRISPR-Cas9 gene disruption or transient suppression of dync1i2a displayed significantly altered craniofacial patterning with concomitant reduction in head size. We monitored cell death and cell cycle progression in dync1i2a zebrafish models and observed significantly increased apoptosis, likely due to prolonged mitosis caused by abnormal spindle morphology, and this finding offers initial insights into the cellular basis of microcephaly. Additionally, complementation studies in zebrafish demonstrate that p.Tyr247Cys attenuates gene function, consistent with protein structural analysis. Our genetic and functional data indicate that DYNC1I2 dysfunction probably causes an autosomal-recessive microcephaly syndrome and highlight further the critical roles of the dynein-1 complex in neurodevelopment.

Biallelic variants in KIF14 cause intellectual disability with microcephaly. - Makrythanasis, Periklis; Maroofian, Reza; Stray-Pedersen, Asbjørg; Musaev, Damir; Zaki, Maha S; Mahmoud, Iman G; Selim, Laila; Elbadawy, Amera; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Gambin, Tomasz; Sorte, Hanne S; et al. (Eur J Hum Genet, 2018)
Kinesin proteins are critical for various cellular functions such as intracellular transport and cell division, and many members of the family have been linked to monogenic disorders and cancer. We report eight individuals with intellectual disability and microcephaly from four unrelated families with parental consanguinity. In the affected individuals of each family, homozygosity for likely pathogenic variants in KIF14 were detected; two loss-of-function (p.Asn83Ilefs*3 and p.Ser1478fs), and two missense substitutions (p.Ser841Phe and p.Gly459Arg). KIF14 is a mitotic motor protein that is required for spindle localization of the mitotic citron rho-interacting kinase, CIT, also mutated in microcephaly. Our results demonstrate the involvement of KIF14 in development and reveal a wide phenotypic variability ranging from fetal lethality to moderate developmental delay and microcephaly.
Keywords: Child; Child, Preschool; Female; Humans; Intellectual Disability; Kinesin; Loss of Function Mutation; Microcephaly; Mutation, Missense; Oncogene Proteins; Pedigree; Phenotype; Protein Domains; Syndrome